Spontaneous coronary artery dissection and its association with heritable connective tissue disorders. Issue 11 (10th February 2016) - Henkin, Stanislav; Negrotto, Sara M; Tweet, Marysia S; Kirmani, Salman; Deyle, David R; Gulati, Rajiv; Olson, Timothy M; Hayes, Sharonne N
Abstract : Objective: Spontaneous coronary artery dissection (SCAD) is an under-recognised but important cause of myocardial infarction and sudden cardiac death. We sought to determine the role of medical and molecular genetic screening for connective tissue disorders in patients with SCAD. Methods: We performed a single-centre retrospective descriptive analysis of patients with spontaneous coronary artery disease who had undergone medical genetics evaluation 1984–2014 (n=116). The presence or absence of traits suggestive of heritable connective tissue disease was extracted. Genetic testing for connective tissue disorders and/or aortopathies, if performed, is also reported. Results: Of the 116 patients (mean age 44.2 years, 94.8% women and 41.4% with non-coronary fibromuscular dysplasia (FMD)), 59 patients underwent genetic testing, of whom 3 (5.1%) received a diagnosis of connective tissue disorder: a 50-year-old man with Marfan syndrome; a 43-year-old woman with vascular Ehlers–Danlos syndrome and FMD; and a 45-year-old woman with vascular Ehlers–Danlos syndrome. An additional 12 patients (20.3%) had variants of unknown significance, none of which was thought to be a definite disease-causing mutation based on in silico analyses. Conclusions: Only a minority of patients with SCAD who undergo genetic evaluation have a likely pathogenic mutation identified on gene panel testing. Even fewer exhibit clinical features of connective tissue disorder. These findings underscore the need for further studies to elucidate the molecular mechanisms of SCAD.